PENINGKATAN AKTIVITAS DAN HASIL BELAJAR IPA MATERI PENYESUAIAN DIRI TUMBUHAN DENGAN LINGKUNGAN MELALUI PENDEKATAN KONTEKSTUAL BAGI SISWA KELAS V SD NEGERI 2 GOMBANG CAWAS KLATEN TAHUN PELAJARAN 2020/2021 - Marini, Marini (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this learning improvement action research is to (1) Improve the activities and learning outcomes of natural science material adapting to plants using a contextual approach for fifth grade students at SD Negeri 2 Gombang for the 2020/2021 academic year. This Classroom Action Research was carried out in two cycles. Each cycle consists of two meetings and is carried out through four stages, namely the planning, implementation, observation and reflection stages. The subjects of this research were 17 class V students at SD Negeri 2 Gombang for the 2020/2021 academic year. The data collection techniques used are observation, tests and documentation. The data analysis technique in this research uses data source triangulation and method triangulation. The results of this research show that applying a contextual approach can improve activities and learning outcomes for students at SD Negeri 2 Gombang for the 2020/2021 academic year. The more actively students participate in the learning process, the higher the grades obtained. In the pre-cycle, the average student score was 61.18 with 35.29% completeness. After implementing the action, cycle I showed an increase in students' activities and learning outcomes, namely the average student score rose to 72.35 with a completeness of 64.71%. In cycle II, the students' average score for understanding the concept of the material peaked to 81.18 with a completeness of 82.35%.